Institutional quality and firm-level financial performance: implications from G8 and MENA Countries - Tarek Ibrahim Eldomiaty; Marina Apaydin; Ahmed El-Sehwagy; Mohamed Hashim Rashwan (Cogent Economics & Finance, 2023)
This paper examines the effects of institutional quality on firm-level financial performance. The data include non-financial firms listed in stock exchanges in G8 and MENA countries. The total number of firms in the G8 and MENA is 347 and 389, respectively, covering the period 2017-2020. The results show that, in the G8 countries, institutional quality is associated significantly and positively with asset efficiency, expense control, debt financing, and liquidity. In the MENA countries, institutional quality is associated significantly and positively with liquidity and profitability, but negatively with asset efficiency, expense control, and debt financing. The results show that the effect of corporate size is asymmetrical. The results also reveal a significant institutional convergence between G8 and MENA countries in terms of voice & accountability, political stability, and government effectiveness. Nevertheless, institutional quality in the G8 is better off that of the MENA countries in terms of Rule of law, Control of Corruption, and Regulatory Quality. The results also show that the duration of improvement in institutional quality takes between 2-4 years to have a significant effect of firms' financial performance. This paper offers a contribution to corporate managers in terms of offering a guide to design financial strategies that adapts to the quality of institutions in the respective countries. A further contribution is offered to policy makers in terms of offering a road map to improve institutional quality that helps improve the financial performance of the business sector.
Keywords: G8; M21; 330; Duration; Firm-level Financial Performance; Institutional Quality; MENA